Clinical utility of and correlation between Sniffin' Sticks and TIB smell identification test (TIBSIT) among Hong Kong Chinese with or without chronic rhinosinusitis - Mak, Hugo W. F.; Ho, Shi Yeung; Wong, Jane C. Y.; Chiang, Valerie; Lee, Elaine; Yim, Jackie S. H.; Wong, Birgitta Y. H.; Li, Philip H. (Frontiers in Allergy, 2024)
Introduction Olfactory dysfunction (OD) is common among patients with chronic rhinosinusitis (CRS). Validated and culturally specific tests, such as the “Sniffin’ Sticks” test (SST) and the TIB Smell Identification Test (TIBSIT), are crucial for the diagnosis and monitoring of OD. However, they have not been utilised in Hong Kong Chinese and their correlations are unknown. Methods Twelve CRS patients and twenty healthy volunteers were prospectively recruited from a joint allergy-otorhinolaryngology clinic in Hong Kong and performed both SST and TIBSIT. Demographics, baseline characteristics and all test results were compared and analysed. Results Patients with CRS demonstrated significantly lower test scores than healthy controls (all p < 0.001). Significant and strong correlations were observed between all composite and subtest scores, particularly between the composite SST and TIBSIT scores (ρ = 0.789, p < 0.001). Multivariate analysis demonstrated that the presence of CRS and increasing age were significantly associated with OD. Conclusion Both SST and TIBSIT are useful olfactory tests and are strongly correlated among Hong Kong Chinese. We advocate that either test can be used for measuring OD among CRS patients.